2006
DOI: 10.1177/112067210601600324
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Disc Edema and Unilateral Macular Hole in a Patient with Retinitis Pigmentosa

Abstract: Inflammatory response in the course of retinitis pigmentosa may result in disc edema and cystoid macular edema, which may further progresses to macular hole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…Inflammatory diseases were ruled out by clinical testing and epidemiologic data (2). Cystoid macular edema is not unusual in RP and improves with carbonic anhydrase inhibitors, as in our cases (3-7); CME due to intraocular inflammation does not typically improve with this treatment. Acute zonal occult outer retinopathy has not been reported in children and presents autofluorescence abnormalities at the peripapillary region which were not found in our cases (8).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Inflammatory diseases were ruled out by clinical testing and epidemiologic data (2). Cystoid macular edema is not unusual in RP and improves with carbonic anhydrase inhibitors, as in our cases (3-7); CME due to intraocular inflammation does not typically improve with this treatment. Acute zonal occult outer retinopathy has not been reported in children and presents autofluorescence abnormalities at the peripapillary region which were not found in our cases (8).…”
Section: Discussionsupporting
confidence: 49%
“…The reduced ERG in these cases ruled out mitochondrial retinal diseases and viral papillitis. Disc swelling can be seen in RP (3, 4, 9). Cancer-associated retinopathy does not present a similar fundus appearance to that of RP.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Furthermore in some cases a recalcitrant, chronic CME that is often associated with RP may also be responsible for MH formation. [1] In our study, among the three patients with RP, two revealed incomplete posterior vitreous detachment and one patient had long standing CME. The surgical results were satisfactory in the patient with CME.…”
Section: Discussionmentioning
confidence: 61%
“…In some patients of RP, associated cystoid macular edema (CME) secondary to chronic ischemia resulting from poorly perfused foveal capillaries may be the predecessor to MH formation. [1] Likewise, a schisis of the inner and outer retinal layers due to chronic leakage from an optic disc pit can result in an outer lamellar or full thickness MH. [2] Other factors responsible for MH formation are traction by condensed vitreous and glial proliferation along the internal limiting membrane (ILM).…”
Section: Introductionmentioning
confidence: 99%
“…Wiadomo, że hipoksja jest odpowiedzialna za powstanie błony nasiatkówkowej i tam ilość zmienionego ciała szklistego była większa. Otwór w plamce natomiast, tam objętość zmienionego ciała szklistego jest mniejsza, był związany raczej z trakcją szklistkowo-siatkówkową (3)(4)(5)(6)(7).…”
Section: Issn 0023-2157 Index 362646unclassified